Intrapersonal externalities: when decisions help or hinder your future self - Stillwell, David J. (2013)
Intrapersonal Externalities are outcomes from a decision which affect the payoffs from future decisions. Positive intrapersonal externalities represent self-investment in one's future self, such as learning a musical instrument or exercising. Negative intrapersonal externalities represent a disinvestment in one's future self, such as eating sugary food or smoking a cigarette. An individual who succumbs to the lure of an immediate payoff in lieu of future potential earnings is considered to be choosing myopically, and it is hypothesised that addictions are one such situation. This failure of the decision-making system to optimise its choices contrasts with delay discounting, in which an individual is assumed to choose rationally but to discount the future, and impulsive disinhibition, in which an individual is assumed to be unable to control their actions even while they state a preference for an action they do not take. This thesis starts by measuring the relationship between delay discounting and impulsive disinhibition with a range of addictive behaviours in a large online study, and finds that while they are consistent predictors there is further variance to explain. It then examines the validity of the intrapersonal externalities model, and finds that it adds independent variance beyond delay discounting and impulsivity in predicting smoking behaviour; there is no evidence that performance in intrapersonal externalities tasks is related to trait impulsivity. It also uses intrapersonal externalities in the laboratory to study advice seeking and taking in an impulsive decision-making context, which would be incompatible with delay discounting or impulsive disinhibition theory. This thesis concludes that the intrapersonal externalities model has been shown to be a viable third model to understand addictive decisions, and suggests that it could be extended to study social addictions.